Photographic techniques for urban art documentation - Pablo Rodriguez-Navarro; Pedro Manuel Cabezos-Bernal; Teresa Gil-Piqueras (Disegnare con)
Urban art or street art, known worldwide as grafﬁti , has become a form of expression, which often has a great visual impact, and now is being part of the image of almost all cities. The majority of these manifestations are carried out illegally, and they consist of a combination of seemingly disjointed texts, whose main aim is to achieve a sensory distraction, a revolutionary or an anti-system act, instead of having an artistic purpose itself. However, there are other graﬃti works that can be considered as masterpieces, since they have an artistic value that is comparable to any piece of art. Another distinctive aspect of graﬃti works is its temporary character, so they are ephemeral and non-conservable pieces, since they are exposed to the climate elements. On the one hand, this fact is not necessarily a problem for the vast majority of graﬃti, but, in the case of a graﬃti masterpiece, it is undeniable that this distinctive feature of mutability, which is an intrinsic part of its artistic objective, should not avoid its correct documentation as a work of art. As its material transience has to be respected, at least, we should document them to preserve its memory and to create a graphic database of urban art masterpieces for future diﬀusion on other media. The main aim of this contribution is to show different photographic methodologies for the doc-umentation of graﬃti on architectural supports. These methodologies have been tested, analysed and evaluated, establishing a suitability criteria according to the conditions in which the works are placed. Finally, some conclusions will be drawn on the diﬀerent documentation methodologies for these urban artworks, which are often photographed both in their sequence and in their ﬁnal art, without having an adequate architectural graphic record. DOI: https://doi.org/10.20365/disegnarecon.24.2020.23